MUTU LAYANAN PENDIDIKAN DI SMKS PERINTIS ADILUHUR - Asep Ali Muhsin (UNISAN JURNAL, 2023)
This study aims to determine: (1) aspects of tangibles, (2) aspects of empathy, (3) aspects of reliability, (4) aspects of responsiveness, and (5) aspects of assurance. , at SMKS Perintis Adiluhur. The approach used in this research is qualitative research with descriptive analysis type. Data from each dimension of service quality in this study were collected through interviews, observation and documentation techniques. Research data were analyzed using triangulation techniques. The results of the study prove that: (1) The quality of service aspects of physical evidence (tangible) is the availability of facilities and infrastructure that support learning, but library facilities and UKS rooms and Conunseling Guidance rooms are not yet available. The SMKS Perintis Adiluhur continues to provide health services and reading room facilities by utilizing unused classrooms. Meanwhile, to overcome the absence of a prayer room by carrying out prayer practices in the classroom. (2) Quality of service aspect of empathy (emphaty) is shown by the concern for service users in this case students, the attention to students who have ability levels below average. (3) Quality of service in the reliability aspect is to provide services that are in accordance with what was promised, any information submitted is accurate and on target. (4) Service quality in the responsiveness aspect of SDN 8 Gedongtataan is indicated by the willingness and ability to help students with difficulties and respond quickly to any input, both criticism and suggestions. (5) Quality of service aspects of assurance (assurance) creates trust and provides assurance to customers that the success rate of the learning process at MtsNahdatulUlama and the output is satisfactory. Adequate teacher competency based on education level and staffing. Guarantees are provided such as the number of graduates reaching one hundred percent, the number of graduates being accepted at public high schools and outstanding academic abilities.